Invitro Antibiotic Activity Of Garlic (Allium Sativum) Extract Against Common Poultry Pathogens - Shamsudeen , P.; Jagadeeswaran, A. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
An investigation was made to assess preliminary phytochemical constituents and in vitro antibiotic activity of garlic extract against common poultry pathogens by agar well diffusion method. Qualitative phytochemical analysis revealed the presence of saponins, terpenoid, flavanoids and volatile oils in garlic. The sensitivity revealed that the Salmonella sp .exhibited more sensitivity at 50 and 100% concentration, equal sensitivity at 25% and lesser sensitivity at 12.5% concentration of garlic than gentamicin and ciprofloxacin. E. coli showed more sensitivity to garlic even at the concentration of 12.5% than the reference antibiotics. Staphylococcus sp. showed lesser sensitivity at 25, 50 and 100% concentrations of garlic than reference antibiotics, whereas it was resistant to garlic at 12.5% concentration.